125Clinical & demographic determinants of self-reported diet program adherence in people living with multiple sclerosis. (2nd September 2021) - Jakaria, Mohamed; Nag, Nupur; Jelinek, George; Weiland, Tracey; Neate, Sandra; Bevens, Will; Simpson-Yap, Steve
Abstract: Background: A range of diets have been recommended for people living with MS, ranging from low or no-meat Swank-inspired diets, to the modified Palaeolithic Wahls diet. While the clinical efficacy of these diets to modulate MS progression is uncertain, the popularity of these diets amongst people living with MS is manifest. Methods: Data derived from the 5-year review of the HOLISM international cohort study. Self-reported adherence to diets were queried, ranging 1-5. Adherence was restricted to ≥ 12months adherence, and then dichotomised: those reporting 4-5/5 adherence defined 2nd-most adherent, 3-5/5 adherence defined 3rd-most adherent. Determinants of adherence were evaluated by log-binomial regression, adjusted for age, sex, socioeconomic status (SES), education, and fatigue. Due to low numbers, only the Overcoming MS (OMS), Swank and Wahls diets were quantitatively evaluated. Results: 458/952 (48.1%) reported following MS-specific diets for ≥12months; 61.8% followed OMS, 12.7% Swank, 3.5% Wahls, 0.9% Ashton-Embry, 0.9% McDougal, 5.7% other. OMS adherence (2nd-most) was more common among males, higher SES, lower disability, less fatigue, and fewer comorbidities. Wahls adherence (2nd-most) was more common among participants with progressive MS or greater disability. Swank adherence (2nd-most) did not vary by any parameter. Analogous results were found using the 3rd-most adherent definition. Conclusions: These results indicate that MS-specific diet adherence is common in this patient population, but uptake is highly heterogenous between demographic and clinical subgroups. Further study of diet uptake among MS patients is indicated, particularly as the efficacy of these diets in MS is yet uncertain. Key messages: There is evidence for a marked tribalisation of diet adherence between the OMS, Swank, and Wahls diets, the former being more common among less clinically active RRMS participants and Wahls more common among more clinically active progressive participants.